The shaping of Russia's Arctic strategy - Fritzen, Johan (Univerzita Karlova, Fakulta sociálních věd, 2022)
The Shaping of Russia's Arctic strategy Abstract Dramatic and rapid shifts are brought about by climate changes to the Arctic geography: Arctic Ocean ice recedes and leave behind resources and sea lanes that traditionally were out of reach to man. This potentially leads to conflict between the coastal states which have overlapping resource claims in the region, different forms of statehood, and diverging security priorities. The changes are felt the strongest in Russia which is investing in Arctic infrastructure to accommodate oil and gas extraction, in addition to a slowly opening intercontinental trade route along her Northern shores. Arctic extraction is a means of increasing economic output and the maritime route to Asia ensures a diversified market which is unlikely to engage in trade sanctions to the same extent as Europe. Melting Arctic ice has repercussions in the defence sphere as well: traditionally protected against invasions from the North by a frozen ocean, Russia's Arctic coastline is becoming exposed to foreign powers. This has sparked a Russian military build-up in the region, inspiring her neighbouring Arctic states to consider their regional defence - not as a response to changed climatic conditions, but to Russia's rhetoric and actions. Both the economic flexibility stemming from Arctic. Utváření ruské arktické strategie Abstrakt Dramatické a rychlé změny v geografii Arktidy způsobují klimatické změny: Led v Severním ledovém oceánu ustupuje a zanechává za sebou zdroje a námořní cesty, které byly tradičně pro člověka nedostupné. To potenciálně vede ke konfliktu mezi pobřežními státy, které mají v regionu překrývající se nároky na zdroje, různé formy státnosti a odlišné bezpečnostní priority. Změny jsou nejsilněji pociťovány v Rusku, které investuje do arktické infrastruktury, aby umožnilo těžbu ropy a zemního plynu a navíc pomalu otevírá mezikontinentální obchodní cestu podél svých severních břehů. Těžba v Arktidě je prostředkem ke zvýšení hospodářského výkonu a námořní cesta do Asie ...